Mapping Research Trends in Sustainable Tourism Development - Judijanto, Loso; Syamsulbahri, Syamsulbahri; Harsono, Iwan (Eastasouth Institute, 2025)
This study aims to map and analyze the research trends in sustainable tourism development using a bibliometric approach. Drawing on data from the Scopus database spanning from 2001 to 2025, the study explores publication growth, leading authors, institutions, countries, and evolving thematic structures in the field. Using VOSviewer for network visualization, the analysis reveals a significant increase in scholarly output, especially after 2017, indicating rising global interest in sustainable tourism as part of broader sustainability agendas. Thematic clustering identifies four major research areas: community-based development, environmental management, economic dimensions of tourism, and regional planning. Overlay and density visualizations show the emergence of recent themes such as climate change, empowerment, and quality of life, reflecting a shift toward more inclusive and resilience-focused perspectives. The co-authorship and country collaboration networks highlight a globally distributed and increasingly interconnected research community, with notable contributions from China, Indonesia, and the United States. This study contributes to a clearer understanding of the field’s intellectual landscape and provides a strategic foundation for future interdisciplinary research and policy-making in sustainable tourism.